Elastomeric impression as a diagnostic method of cavitation in proximal dentin caries in primary molars - Adriela Azevedo Souza Mariath; Ana Eliza Lemes Bressani; Fernando Borba de Araujo (University of São Paulo, 2007)
The purpose of this study was to validate the elastomeric impression after temporary tooth separation as a method of cavitation detection in proximal caries lesions in primary molars with outer half dentin radiolucency. Fifty-one children (4-10 years old), presenting radiolucency in the outer half of the dentin at the proximal surfaces of primary molars and proximal anatomic contact with the adjacent tooth (without restoration/cavitated caries lesion) were enrolled in the study. Temporary tooth separation was performed with an orthodontic rubber ring placed around the contact point during 2-3 days. Thereafter, impression of the proximal surfaces was made. The elastomeric impressions were classified as "non-cavitated" or "cavitated" surfaces. Visual inspection after tooth separation was considered as the gold standard. Examiner reliability of visual inspection after tooth separation was determined (kappa 0.92). Impression examination was repeated every 5 participants to evaluate the reproducibility of the method. The frequency of cavitated lesions was 65%, and 67% of those were inactive. Sensitivity, specificity, positive and negative predictive values were 0.88% (95%CI 0.73-0.95), 0.89% (95%CI 0.67-0.97), 0.94% (95%CI 0.79-0.98) and 0.80% (95%CI 0.58-0.92), respectively. Impression examination showed total agreement regarding cavitation. The evaluation of elastomeric impression after tooth separation is a useful clinical resource in cavitation detection for clinicians and researchers when visual inspection is doubtful.